Enablers and Barriers to Green Supply Chain Management with TOPSIS and MOORA for Prioritzing Decision-Making - Eng Yennylawati; Mustafid Mustafid; Adian Fatchur Rochim (Diponegoro University, 2025)
Indonesia is the world’s largest coconut producer. As a result, coconuts play an important role in sustaining millions of Indonesians' livelihoods. In 2021, a fear of cooking oil emerged, leading to a decline in production levels, reduced income for individuals, and an increase in commodity pricing both domestically and internationally. The scarcity of cooking oil, notwithstanding Indonesia's position as the leading global producer, indicates an imbalance between supply and demand. This research aims to investigate production problems as the root cause of coconut industry shortages, identify productivity-related issues through a literature review, and assess the urgency of the criteria presented in five Linkert scales. Listing problems is critical for determining the root of the problem, as well as the potential for increasing revenue and ensuring long-term sustainability through value-added initiatives in the green supply chain management (GSCM) scope. This study uses TOPSIS and MOORA analysis, a way of making decisions based on levels of importance and enabler barriers in the coconut industry, focusing on production and productivity.